Faktor-Faktor Yang Mempengaruhi Partisipasi Terhadap Petani Terhadap Program Asuransi Usaha Tani Padi (AUTP) Di Kecamatan Sukamakmur - Khumaira, K; Puspita, Diah Eka (LPPM Universitas Malikussaleh - Indonesia, 2019)
This study aims to analyze the level of participation of farmers at the implementation stage and the stage of yield utilization in the AUTP (Rice Farming Insurance) program and analyze the influence of farmers' understanding / knowledge factors on AUTP, socialization of agricultural extension workers, the amount of premiums paid, the number of claims received against participation farmers in the AUTP program. This research was conducted in the District of Sukamakmur, Aceh Besar district with the method of determining respondents using simple random sampling. The number of samples analyzed in this study totaled 55 people in 4 study villages. This study uses a quantitative approach. Analyze the level of farmer participation in the AUTP program calculated using an ordinal scale and to analyze the factors that influence the participation of farmers in the AUTP program using the Spearman correlation test. Based on the analysis of high farmer participation rates, it can be concluded that farmers have realized the importance of AUTP for the sustainability of their farming so that they voluntarily want to participate in the AUTP program. Based on the correlation relationship, it can be concluded that farmers' understanding / knowledge of AUTP, socialization of agricultural instructors, the number of claims received has a positive correlation with the level of participation